A meta-analysis of birth-origin effects on reproduction in diverse captive environments - Katherine A. Farquharson (Nature Portfolio, 2018)
Aquaculture, conservation, and biological research are reliant on the successful breeding of animals in captivity. Here, Farquharson et al. report that, in captivity, captive-born animals have decreased reproductive success compared to wild-born individuals, across diverse species and contexts.